Role perceptions, actualizations and expectations among administrators, counselors and teachers in relation to the guidance programs of secondary schools in Cebu City, 1973-1974 - Tallo, Veronica Legaspi 1951- (1974)
This study determined the role perceptions, actualizations and expectations of administrators, counselors and teachers in relation to the guidance program of the secondary schools in Cebu City. This study further examined the similarities and differences in the role perceptions and expectation responses of the three groups of respondents in the study.
Thesis (M.Ed.)--University of the Philippines
Keywords: Personnel service in education -- Cebu City